34th IEEE Sarnoff Symposium 2011
DOI: 10.1109/sarnof.2011.5876468
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency gains in interference-limited heterogeneous cellular mobile radio networks with random micro site deployment

Abstract: Abstract-Energy efficiency considerations recently gained attention due to ecological aspects, that is to say lowering CO2 emissions and reducing energy consumption. Furthermore, it is important to assess energy efficiency improvements from an operator's point of view, since energy costs are increasing and providing ubiquitous high speed mobile access may scale up the operators' operational expenditure. One of two promising approaches to enhance a network's operation regarding energy efficiency is to utilize s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…By contrast, Wu et al [11] investigated the impact of the average delay of services on the total power consumption for a single BS site. Furthermore, by introducing an EE metric, the impacts of key network parameters, including the number of BSs in a given area, power amplifier with delay and mobile traffic demand, are evaluated based on system-level simulation [13]- [15]. Additionally, the work [16] maximizes the EE by joint power and subcarrier allocation for a single-cell OFDMA network with multiple relays.…”
Section: A Related Workmentioning
confidence: 99%
“…By contrast, Wu et al [11] investigated the impact of the average delay of services on the total power consumption for a single BS site. Furthermore, by introducing an EE metric, the impacts of key network parameters, including the number of BSs in a given area, power amplifier with delay and mobile traffic demand, are evaluated based on system-level simulation [13]- [15]. Additionally, the work [16] maximizes the EE by joint power and subcarrier allocation for a single-cell OFDMA network with multiple relays.…”
Section: A Related Workmentioning
confidence: 99%
“…The area power consumption (defined as the amount of power used per unit area) was obtained as a function of the inter-site distance and it was found that there is an optimum value that minimizes this metric. A more general case was investigated in [19] where system throughput, area power consumption and EE were compared between a homogeneous network (only macro-cells deployed) and a heterogeneous network (consisting of both macro and microsites). In this case, the micro-cells were uniformly positioned near the border of each macro-cell, which accounts for a more realistic scenario, as the micro-cells will serve particular areas where the capacity or coverage needs to be improved, which will not necessarily only be at the edge of a macrocell.…”
Section: B Related Workmentioning
confidence: 99%
“…According to [1], cellular network worldwide consumes approximately 60 billion kWh per year, among a promising avenue to reduce CO 2 emission and on-grid power consumption, e.g., the technique report [4] and the technique specification [5] of 3rd Generation Partnership Project (3GPP) clearly indicate that the use of renewable energy resources is explicitly encouraged in mobile network, and researching on it is suggested to have high priority.…”
Section: Introductionmentioning
confidence: 99%